Buyang Huanwu decoction improves neural recovery after spinal cord injury in rats through the mTOR signaling pathway and autophagy. (2nd January 2023) - Nie, Ying; Fan, Yujie; Zhang, Xi; Li, Xiaosong; Yin, Jian; Li, Meili; Hu, Zhaoyong; Li, Liang; Wang, Xiaoye
Abstract : Background: Spinal cord injury (SCI) refers to the interruption of the tracts inside the spinal cord caused by various factors. The repair of damaged axons has always been a difficult point in clinical treatment and neuroscience research. The treatment of SCI with Buyang huanwu decoction (BYHWD), a well-known recipe for invigorating Qi (a vital force forming part of any living entity in traditional Chinese culture) and promoting blood circulation, shows a good effect. Methods: The rubrospinal tract (RST) transection model in rats was established in this study and rats were administrated with low (BL), medium (BM), or high (BH) doses of BYHWD. Results: Compared with the SCI group, BL, BM moderately, and BH significantly improved the motor function of forelimbs and increased the number of red nucleus neurons in SCI rats. As for the possible molecular mechanism, BL, BM moderately, and BH significantly increased mTOR whereas decreased Beclin-1 and LC3 in the red nucleus. Conclusion: In conclusion, low, medium, and high doses of BYHWD could promote neural recovery in SCI rats through improving motor function and neuron survival in the red nucleus. The neuroprotective effects of BYHWD might be associated with affecting the mTOR signaling pathway and autophagy.